Understanding Consumer Preferences for Tangerines (Citrus reticulata) in Urban Traditional Markets: Evidence from Surakarta, Indonesia - Lia Maharani; Mahananto; Kusriani Prasetyowati; Adhisty Puri Damayanti (Agribusiness Department, Agriculture Faculty, Tunas Pembangunan University, Surakarta, Indonesia, 2026)
Citrus fruit is one of the fruits favored by the people of Indonesia because this fruit is easy to find anywhere and anytime and can be consumed by various circles of society, both the upper, middle and lower classes. Tangerine (Citrus reticulata) is one of the Citrus that lives in tropical and subtropical regions.This study aims to examine the attributes of tangerines that are consumer preferences in the traditional market of Surakarta City and examine the attributes of tangerines that are most considered by consumers in the decision to buy tangerines in the traditional market of Surakarta City. The method of determining the location uses a purposive method and the sampling method is carried out by accidental sampling, the determination of the number of respondents in each traditional market is determined proportionally to the number of respondents as many as 50 respondents. The data analysis method used is chi square analysis and multi-attribute Fishbein. The results of this study indicate that the tangerines that are consumer preferences in the traditional market of Surakarta City are tangerines that have a sweet taste, medium fruit prices (20,000-24,900), orange skin color and have medium fruit sizes (8-9 pieces/year). kg). The attribute of tangerines that is most considered in the decision to buy tangerines in the traditional market of Surakarta City is the attribute of sweetness. The order of attributes from the most considered to the least considered is fruit taste, fruit price, fruit skin color, and fruit size.